Frequency Hopping Acquisition Based on Variable Forgetting Factor Recursive Least Squares Algorithm - Chen, Zengmao; Zhao, Xianwu; Lu, Li; Sun, Rongchen; Sun, Zhiguo (2022 IEEE 12th Annual Computing and Communication Workshop and Conference (CCWC), 2022)
The main drawback of frequency hopping pattern synchronization capture algorithms is time-consuming. To address this problem, variable forgetting factor recursive least square (VFFRLS) frequency hopping pattern acquisition algorithm is proposed in this paper. First, the coefficients of the adaptive spectrum estimation model are calculated iteratively used the VFFRLS algorithm. Then, instantaneous frequency of the frequency hopping signal is estimated, and the result is converted into a binary sequence. The most significant bit of the binary sequence is loaded into the linear feedback shift register. Finally, the correct frequency point could be obtained. The theoretical expressions of bit error rate, capture probability and average capture time are derived under the Additive White Gaussian Noise environment. Moreover, the capture performance is verified through numerical simulation.